KESESUAIAN PERTIMBANGAN HAKIM DALAM PUTUSAN NOMOR 1/Pid.Sus-Anak2022/PN BYL DENGAN UU SPPA - Azzam Zaid Muharam; Bambang Santoso (Sebelas Maret University, 2023)
This writing analyzes the suitability of the judge's considerations in imposing a prison sentence of two years and three months of job training for children with Article 71 paragraph (3) and Article 79 of the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Justice System. In Decision Number 1/Pid.Sus-Anak/2022/PN Byl it is known that there has been a criminal act of sexual intercourse with a child, which was committed by a child. Child offenders are subject to Article 81 paragraph (2) of Law Number 17 of 2016 concerning Stipulation of Government Regulation in lieu of Law Number 1 of 2016 regarding the second amendment to Law Number 23 of 2002 concerning Child Protection. The Child Protection Act can be applied to anyone, regardless of whether the offender is an adult or a child. So to protect child perpetrators, the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Justice System is enacted. The purpose of this writing is to find out whether the judge's considerations in Decision Number 1/Pid.Sus-Anak/2022/PN Byl are in accordance with the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Justice System. As a result, the judge in his considerations before making a decision had considered Article 71 paragraph (3) of the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Justice System. Keywords: Consideration; Intercourse; Child